Effect of the Direct Oral Anticoagulants Rivaroxaban and Apixaban on the Disposition of Calcineurin Inhibitors in Transplant Recipients. Issue 1 (February 2017) - Vanhove, Thomas; Spriet, Isabel; Annaert, Pieter; Maertens, Johan; Van Cleemput, Johan; Vos, Robin; Kuypers, Dirk
Abstract : Background: Calcineurin inhibitors (CNIs) and direct oral anticoagulants (DOACs) share certain metabolic pathways, but whether DOACs influence CNI exposure has not been assessed. Methods: A single-center retrospective analysis was performed including 39 organ recipients treated with the combination of a CNI and rivaroxaban (n = 29) or apixaban (n = 10). Dose-corrected CNI trough concentrations (C0/D) during 200 days before and after DOAC initiation were recorded (n = 261), together with covariates known to influence CNI disposition such as steroid dose and hematocrit. The average C0/D before and during DOAC therapy was compared using paired samples t test. Multivariable mixed models were constructed to estimate the effect of DOAC and other predictors on C0/D at each time point. Results: Group average C0/D was not significantly different before and during DOAC therapy for any CNI–DOAC combination ( P = 0.089–0.761), although C0/D changed >20% in 19/39 patients (13 increases, 6 decreases). In multivariable analysis, independent predictors of tacrolimus C0/D were methylprednisolone dose ( P = 0.039) and concomitant use of a CYP3A inhibitor ( P = 0.007). The subgroup analysis per DOAC showed a limited but significant effect of rivaroxaban on tacrolimus C0/D (9.2% increase, P = 0.042). Independent predictors of ciclosporin C0/D were age ( P = 0.018) and use of any DOAC (12.1% increase, P = 0.020). Conclusions: Apixaban, and particularly rivaroxaban, may cause a limited (<20%) increase in CNI trough concentration, an effect that is unlikely to trigger a dose change. It may be prudent to perform an additional CNI trough concentration measurement 5–7 days after DOAC initiation, but preemptive CNI dose changes are not warranted based on these observations. Abstract : Supplemental Digital Content Is Available in the Text.